Effectiveness of combined exercise and nutrition interventions in prefrail or frail older hospitalised patients: a systematic review and meta-analysis. Issue 12 (13th December 2020) - Han, Chad Yixian; Miller, Michelle; Yaxley, Alison; Baldwin, Claire; Woodman, Richard; Sharma, Yogesh
Abstract : Objectives: To determine the effectiveness of combined exercise-nutrition interventions in prefrail/frail hospitalised older adults on frailty, frailty-related indicators, quality of life (QoL), falls and its cost-effectiveness. Design: Randomised controlled trials (RCTs) of combined exercise-nutrition interventions on hospitalised prefrail/frail older adults ≥65 years were collated from MEDLINE, Emcare, CINAHL, Ageline, Scopus, Cochrane and PEDro on 10 October 2019. The methodological quality was appraised, and data were summarised descriptively or by meta-analysis using a fixed effects model. The standardised mean difference (SMD) or difference of means (MD) with 95% CIs was calculated. Results: Twenty articles from 11 RCTs experimenting exercise-nutrition interventions on hospitalised older adults were included. Seven articles were suitable for the meta-analyses. One study had low risk of bias and found improvements in physical performance and frailty-related biomarkers. Exercise interventions were mostly supervised by a physiotherapist, focusing on strength, ranging 2–5 times/week, of 20–90 min duration. Most nutrition interventions involved counselling and supplementation but had dietitian supervision in only three studies. The meta-analyses suggest that participants who received exercise-nutrition intervention had greater reduction in frailty scores (n=3, SMD 0.25; 95% CI 0.03 to 0.46; p=0.02) and improvement in short physical performance battery (SPPB) scores (n=3, MD 0.48; 95% CI 0.12 to 0.84; p=0.008) compared with standard care. Only the chair-stand test (n=3) out of the three SPPB components was significantly improved (MD 0.26; 95% CI 0.09 to 0.43; p=0.003). Patients were more independent in activities of daily living in intervention groups, but high heterogeneity was observed (I 2 =96%, p<0.001). The pooled effect for handgrip (n=3)±knee extension muscle strength (n=4) was not statistically significant. Nutritional status, cognition, biomarkers, QoL, falls and cost-effectiveness were summarised descriptively due to insufficient data. Conclusions: There is evidence, albeit weak, showing that exercise-nutrition interventions are effective to improve frailty and frailty-related indicators in hospitalised older adults.